Exploration of the inhibition action of TPGS on tumor cells and its combined use with chemotherapy drugs. (31st December 2023) - Tang, Lan; Huang, Kaijuan; Jiang, Wenhui; Fu, Lulu; Zhang, Ran; Shen, Liting; Ou, Zhimin; Huang, Ye; Zhang, Zhenhai
Abstract: D-alpha-tocopheryl polyethylene glycol 1000 succinate (TPGS) is a commonly used nonionic surfactant used as a pharmaceutical carrier in different drug delivery systems. TPGS can reverse P-glycoprotein (P-gp)-mediated multidrug resistance (MDR) and also has anticancer activities. It suggests that when designing antitumor drug preparation, it's necessary to take into account the antitumor activity of TPGS. Our in vivo studies showed that TPGS exerted the strongest cytotoxicity in MCF-7-ADR cells when compared with seven other tumor cell lines. The further study revealed TPGS caused apoptosis and blocked MCF-7 cell growth in G2/M phase. Mechanistic insights suggested that TPGS increased intracellular calcium ion concentrations, leading to apoptosis via the mitochondrial pathway. Furthermore, two in vivo experiments were performed. One was TPGS, and DOX solution was administered by tail vein injection on MCF-7-ADR tumor bearing nude mice. The other was temperature sensitive TPGS gel (TPGS-TG) was administered by intratumoral injection on MCF-7-ADR tumor bearing nude mice combined with paclitaxel albumin nanoparticles (Abraxane ® ) administered by tail vein injection. The findings confirmed that TPGS could play its role in anti-tumor to reduce the toxicity of chemotherapeutic drugs and improve the efficiency of drug-resistant tumors, thereby enhancing the development of safe oncology therapeutics. Abstract : UF0001